2007
DOI: 10.3181/0702-rm-31
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin and β-Lapachone Release and Interaction with Micellar Core Materials: Experiment and Modeling

Abstract: Polymer micelles with two different core-forming blocks, poly(d,l -lactide) (PLA) and poly(epsilon-caprolactone) (PCL), but the same coronal material, poly(ethylene glycol) (PEG), were investigated in this study as nanoscopic drug carriers. The release of two different drugs, doxorubicin (DOX) and beta-lapachone (beta-lap), from PEG(5k)-b-PCL(5k) and PEG(5k)-b-PLA(5k) micelles was studied at pH 5.0 and 7.4. Mathematical solutions of both Higuchi's model and Fickian diffusion equations were utilized to elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 51 publications
5
52
0
Order By: Relevance
“…Recently, polymeric micelles have been emerged as a novel nanomedicine platform for drug delivery, due to their smaller size, stability, versatility, and biocompatibility (Shen et al, 2007;Sutton et al, 2007). These micelles have demonstrated their ability to efficiently solubilize lipophilic agents with altered drug pharmacokinetics and in several cases have been reached to clinical trials (Allen et al, 2000;Matsumura et al, 2004;Zhang et al, 2004;Forrest et al, 2008;Lee et al, 2008;Xiong et al, 2008) Micelles made up of core-shell structure are normally fabricated by a self-assembly approach using amphiphilic block copolymers in a selective solvent in which the hydrophobic core part provides a cargo space for solubilization of various lipophilic drugs (Aliabadi et al, 2007;Molavi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, polymeric micelles have been emerged as a novel nanomedicine platform for drug delivery, due to their smaller size, stability, versatility, and biocompatibility (Shen et al, 2007;Sutton et al, 2007). These micelles have demonstrated their ability to efficiently solubilize lipophilic agents with altered drug pharmacokinetics and in several cases have been reached to clinical trials (Allen et al, 2000;Matsumura et al, 2004;Zhang et al, 2004;Forrest et al, 2008;Lee et al, 2008;Xiong et al, 2008) Micelles made up of core-shell structure are normally fabricated by a self-assembly approach using amphiphilic block copolymers in a selective solvent in which the hydrophobic core part provides a cargo space for solubilization of various lipophilic drugs (Aliabadi et al, 2007;Molavi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The type of polymers used produced noticeable effect on the size of micelles where the size of PEG-b-PCL micelles was smaller than that of PEG-b-PLA; this was due to the more hydrophobic property of PEG-b-PCL that lead to less swollen structure and more compact micelle core. 14) Micelle size, drug loading contents (% DLC), encapsulation efficiency (% EE) and yields (% yields) of AG50-loaded PEG-b-PCL and PEG-b-PLA micelles were shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular weight of these copolymers can be varied which in turn controls the particle size, drug encapsulation, and drug release of the polymeric micelles. 13,14) Several methods for micelle preparations have been examined to encapsulate hydrophobic drug in polymeric micelles. Solvent evaporation method, film sonication, and dialysis method are widely used for micelle preparation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the above copolymerization can be depicted as in Scheme 1(with LA instead of CL). 13 C NMR spectrum of PLA-b-PEG-b-PLA ( Figure 5) showed peaks at 169.3 and 174.30 ppm attributed to the carbonyl group of the polyester blocks and peaks at 17.3 and 69.5 ppm attributed respectively to methyl and methine carbon atoms. First investigations based on 13 C NMR analysis also indicated that the stereochemistry of the chiral carbon atom of the L-lactide monomer CO-CH(CH 3 )-O was unchanged during the polymerization leading to the formation of stereoregular sequence as P(L-LA).…”
Section: N Nmr = M N Peg + (M N Peg /44 X 72 X 4 X I Ch3 (La) /I Chmentioning
confidence: 99%